Indicators of the Structural and Functional State of the Left Ventricle Depending on the Type of Its Geometry in Patients with Arterial Hypertension According to Tissue Doppler Echocardiography Data - Saodat Yarmukhamedova et al. (International Journal of Control and Automation, 2020)
The concept of "hypertensive heart" includes structural and functional rearrangement of the left ventricle, which is accompanied by impaired diastolic function and can cause the development of chronic heart failure with preserved systolic myocardial function. According to the data obtained, in patients with arterial hypertension, regardless of the presence of left ventricular hypertrophy, there is a significant, compared with the control group, a slowdown in the time of isovolumic relaxation and a decrease in the ratio of the peak velocities of the early and late diastolic waves due to an increase in the peak velocity of the late diastolic wave, but more pronounced in the presence of left ventricular hypertrophy. It should be noted that the revealed changes in the transmitral blood flow in patients with AH in the absence of LVH did not go beyond the normative values, while in the presence of hypertrophy, a decrease in the E / A ratio <1 and, especially, an increase in the Tei-index indicate a violation of the diastolic function of the myocardium due to its deterioration. elastic properties. The development of left ventricular hypertrophy was also significantly more often accompanied by a violation of the diastolic function of the myocardium. Thus, signs of impaired relaxation of the left ventricle were significantly more frequently observed in patients with arterial hypertension with left ventricular hypertrophy, while the normal diastolic function of the myocardium was more often preserved in its absence. A pseudonormal type of left ventricular diastolic dysfunction was detected in 9 (15.0%) patients in the group with left ventricular hypertrophy. In case of left ventricular hypertrophy, the most sensitive method for assessing the functional state of the myocardium is tissue Doppler echocardiography, which, at the stage of compensatory myocardial hypertrophy in patients with arterial hypertension, reveals not only violations of the diastolic function of the myocardium, but also regional disorders of systolic function in the anterior and lateral walls of the left ventricle ... Disorders of left ventricular diastolic function according to tissue Doppler echocardiography are characterized by a decrease in the peak velocity of early diastolic myocardial movement with an increase in the time of its slowdown in the region of the anterior, lateral and inferior walls of the left ventricle. Tissue Tei-index is a more sensitive marker of myocardial functional state disorder than Tei - index of transmitral blood flow.